2011
DOI: 10.3892/or.2011.1476
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin antisense oligodeoxynucleotides induce apoptosis and may be used as a potential drug for nasopharyngeal carcinoma therapy

Abstract: Abstract. Nucleolin (C23, NCL) mRNA was up-regulated in nasopharyngeal carcinoma (NPC) cells compared to that of normal nasomucosal (NNM) cells using a cDNA microarray approach. The level of nucleolin protein was also up-regulated in 13 NPC cell lines, 30 biopsy specimens and nine other cancer cell lines compared to five NNM cells or normal stromal cells, which were analyzed using immunoblotting or immunohistochemistry. We transfected nucleolin antisense oligodeoxynucleotides (phosphorothioate-modified oligode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Decreased nucleolin expression also caused a dramatic decrease of tumor size in an intracranial xenograft model. Wu et al 34 showed that antisense phosphorothioate-modified oligodeoxynucleotides (S-ODNs) directed at nucleolin mRNA could trigger the apoptosis of nasopharyngeal carcinoma (NPC) cells and that S-ODN treatment would result in the suppression of NPC growth in tumor xenografts. It was also reported that upon binding of miRNA-494 to nucleolin, nucleolin expression was inhibited and led to an obvious reduction of cancer cell survival.…”
Section: Nucleolin-based Sirna and Microrna Treatmentmentioning
confidence: 99%
“…Decreased nucleolin expression also caused a dramatic decrease of tumor size in an intracranial xenograft model. Wu et al 34 showed that antisense phosphorothioate-modified oligodeoxynucleotides (S-ODNs) directed at nucleolin mRNA could trigger the apoptosis of nasopharyngeal carcinoma (NPC) cells and that S-ODN treatment would result in the suppression of NPC growth in tumor xenografts. It was also reported that upon binding of miRNA-494 to nucleolin, nucleolin expression was inhibited and led to an obvious reduction of cancer cell survival.…”
Section: Nucleolin-based Sirna and Microrna Treatmentmentioning
confidence: 99%